Aggressiveness of Differentiated Thyroid Carcinoma in Pediatric Patients Younger Than 16 years: A Propensity Score-Matched Analysis - Kim, Soo Young; Yun, Hyeok Jun; Chang, Hojin; Kim, Seok-Mo; Jeon, Soyoung; Lee, Sujee; Lee, Yong Sang; Chang, Hang-Seok; Park, Cheong Soo (Frontiers in Oncology, 2022)
Background: The biological behavior of thyroid cancer in children has been known to be different from that in adults. We sought to understand the differences between DTC presentation in pediatric (<16 years) and adult patients, to guide better prognosis and clinical treatments. Methods: This retrospective study included 48 pediatric patients younger than 16 years who underwent initial thyroid surgery and were diagnosed with DTC between January 1992 and December 2014 at Yonsei University in Seoul, South Korea. For a 1:4 propensity score-matched analysis, adult patients with matched sex and cancer size were included. Results: The mean age was 12.54 3.01 years. Total thyroidectomy (70.8%) without lateral lymph node dissection (47.9%) was the most commonly performed surgery. Central (73.9%) and lateral neck node metastases (62.5%) were common; distant metastasis was observed in 2 (4.2%) patients and recurrence occurred in 11 (22.9%). In propensity score-matched analysis, central lymph node metastasis and lateral neck node metastasis were significantly more frequent in pediatric patients. Symptoms were more common in the pediatric group than in the adult group (p < 0.001). In stratified cox regression, pediatric patients were more likely to experience recurrence [HR 5.339 (1.239–23.007)]. In stratified log-rank analysis, recurrence-free survival was significantly different between the adult and pediatric groups (p = 0.0209). Conclusion: DTC in the pediatric group revealed more aggressive patterns than in the adult group with the same cancer size. Central lymph node metastasis and lateral neck node metastasis were more frequent. Stratified log-rank analysis revealed that recurrence was significantly higher in pediatric patients than in matched adult patients.